Multiple re-entry gunshot wounds possibly inflicted by a single shot: Case report - Çağdaş Savaş; Emir Derkuş; Umut Erdar Bilgin; İsmail Özgür Can (Forensic Science Today - Peertechz Publications, 2020)
Fireguns continue to attract people's attention today as they have in the past. People obtain fireguns for individual purposes such as hunting, protection or defense. Again, firearms are manufactured for institutional purposes and used for deterrence, defense, and even for attacking in order to eliminate danger and threat [1].